(C) Both (A) and (B)
Step-by-step explanation
Step 1
a function where y is a function of x is given by:
![y=f(x)](https://img.qammunity.org/qa-images/2023/formulas/mathematics/high-school/57cr0i5h972yqnnq2tfd.png)
isolating y in (A)
![\begin{gathered} 3y^4+2x-7=1 \\ 3y^4=1-2x+7 \\ 3y^4=-2x+8 \\ y^4=(-2x+8)/(3) \\ y=\pm\sqrt[4]{-2x+8} \\ \\ \end{gathered}](https://img.qammunity.org/qa-images/2023/formulas/mathematics/college/caaqliqeq1297zmcxaqm.png)
then, A is a function
Step 2
isolating y in (B)
![\begin{gathered} x^2y+x=4y \\ +x=4y-x^2y \\ x=y(4-x^2) \\ y=(x)/(4-x^2) \end{gathered}](https://img.qammunity.org/qa-images/2023/formulas/mathematics/college/luhj7bvtiepixmbeckl2.png)
then, (B) is an equation that represents y as a function on x
I hope this helps you.